Urethral Foreign Body Management: A Case Report - Islam, Md Nazrul Al; kashem, Ma (Bangladesh Journal of Urology, 2020)
Abstract Not Available Bangladesh Journal of Urology, Vol. 19, No. 2, July 2016 p.103-104